Motor Performance in Children Diagnosed with Cancer: A Longitudinal Observational Study - Lotta Hamari; Päivi M Lähteenmäki; Heidi Pukkila; Mikko Arola; Anna Axelin; Sanna Salanterä; Liisa S Järvelä (MDPI, 2022)
Children with cancer are dealing with different side and long-term effects caused by cancer and its treatments, like vinca-alkaloids, which may have negative effects on motor performance. However, the affected areas of motor performance (aiming and catching, balance, manual dexterity) and the differences in these areas between boys and girls and diagnoses are not frequently reported in a longitudinal design. Therefore, the aim of this study was to investigate how motor performance changes over the course of cancer treatment. The study was conducted with 3-to 16-year-old children with cancer (N = 36) in 2013-2017. The five assessment points were 0, 2, 6, 12 and 30 months from diagnosis. Movement-ABC2 was used to assess motor performance. We found that aiming and catching skills decreased significantly during the follow-up (p < 0.05). Balance was affected at the 2-month measurement point (p < 0.05) and more in children with acute lymphoblastic leukemia than in children with other cancer diagnoses (p < 0.05). Girls performed better than boys in manual dexterity at 6, 12 and 30 months (p < 0.05, p < 0.05, p < 0.05, respectively). Individual monitoring of motor performance with standardized tests and physical activity/exercise programs during and after treatment are needed.